Sustainability of teaching staff of Medicine program in Cienfuegos - Julia Megris Hernández Mompie; Mabel Rocha Vázquez; Vivian Lima Navarro (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2020)
Introduction: The development achieved by the faculty cloister is an indispensable requirement that denotes the quality of an academic program or institution and its sustainability is a priority at present. Objective: to determine the current state of sustainability of the faculty cloister in the Medical Program of the Faculty of Medical Sciences of Cienfuegos. Methods: pedagogical research developed at the University of Medical Sciences Of Cienfuegos in the period January 2018 to December 2019. Theoretical and empirical methods were applied that together allowed to characterize the object of study. Interviews were conducted with academic managers, group dynamics, documentary review and triangulation to identify regularities. Results: The race cloister exhibits indicators that depart from the current quality criteria and the necessary generational respite is not identified to ensure sustainability. Discussion: The cloister in the Medical Program of the Faculty of Medical Sciences of Cienfuegos is not sustainability because of it characteristics and the actions to maintain and to increase its level, besides the trend to actual and future progress progress, things which deserve to be attended in order to get changes.